Potentialities of human beings and creative music making: reflections based on the shift in emphasis from knowledge to thinking (Orfeu, 2021)
Belonging to the field of Music Education, this article aims to present a theoretical discussion about creative practices and takes as its basis the concept of shifting the emphasis from “knowing to think”, proposed by Boris Porena. The text is divided into three parts. The first considers studies carried out with babies, to deal with “communicative musicality”. The second addresses Porena’s thinking, in order to explain the meanings of the proposition “from knowing to think” and the relationship that this thinking has with the author’s practical proposals. Finally, some aspects of John Paynter’s thought are discussed by the perspective of the problem. It is concluded that these approaches, although diverse, converge towards a common point: the shift of the emphasis from “knowing to think” through creative practices, in order to consider the musical potential of the human being and his ways of being and be in the world.
Keywords: Music education; Creative practices; Communicative musicality; Boris Porena; John Paynter